2003
DOI: 10.1242/jcs.00368
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Ca2+ cycling by the plasma membrane Ca2+-ATPase increases the `excitability' of the extracellular Ca2+-sensing receptor

Abstract: IntroductionThe extracellular Ca 2+ -sensing receptor (CaR) is a cell surface receptor for divalent cations whose existence was originally suspected in the parathyroid gland (Brown et al., 1987;Nemeth and Scarpa, 1987;Shoback et al., 1988). Cloning of the receptor by Brown and colleagues (Brown et al., 1993) confirmed the essential role of CaR as a Ca 2+ sensor in the parathyroid, and also set the stage for the identification of the receptor in a wide variety of tissues not involved in systemic Ca 2+ homeostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…In clusters of cultured HEK-293 cells, various extracellular stimuli give rise to oscillations in [Ca 2+ ] cyt that correlate with oscillations in [Ca 2+ ] ext ; it is possible that CaSR is involved in generating and in decoding calcium oscillations [36].…”
Section: Calcium As An Extracellular Messenger In Eukaryotesmentioning
confidence: 99%
“…In clusters of cultured HEK-293 cells, various extracellular stimuli give rise to oscillations in [Ca 2+ ] cyt that correlate with oscillations in [Ca 2+ ] ext ; it is possible that CaSR is involved in generating and in decoding calcium oscillations [36].…”
Section: Calcium As An Extracellular Messenger In Eukaryotesmentioning
confidence: 99%
“…In co-cultures of HEK CaR-bearing 'sensor' cells and other 'donor' cells (e.g. fibroblasts) grown under an artificial polypropylene mesh to minimize the volume of extracellular fluid, stimulation of donor cells with a Ca 2+ -mobilizing agonist that does not bind to the sensor cells activates adjacent HEK CaR-bearing sensor cells (Hofer et al, 2000;Thomas, 2000 (Belan et al, 1998;De Luisi and Hofer, 2003), and this might repetitively stimulate CaR on the same or a neighboring cell (Gracheva and Gunton, 2003). Since intracellular [Ca 2+ ] oscillates vigorously in HEK CaR cells during CaR activation (Breitwieser and Gama, 2001;De Luisi and Hofer, 2003;Young and Rozengurt, 2002) (Fig.…”
Section: Camentioning
confidence: 99%
“…However, it produces an endothelium-dependent relaxation in intact rings of rat aorta (0.34 mM) (Chaudhary et al, 2001). Caloxin does not inhibit Mg 2ϩ -ATPase or Na ϩ /K ϩ -ATPase (Holmes et al, 2003) and has been shown to also inhibit PMCA activity in human mesenchymal stem cells (Kawano et al, 2003) and human embryonic kidney (HEK) cells (De Luisi and Hofer, 2003 ATPases, which occur predominantly in the Golgi compartment of eukaryotic cells (reviewed by Wuytack et al, , 2003. The rise of intracellular Ca 2ϩ is vital to cell function, but Ca 2ϩ availability must occur rapidly and in sufficient concentration at required intracellular targets.…”
Section: B Sarcoplasmic Reticulummentioning
confidence: 99%